The Ala16Val MnSOD gene polymorphism modulates oxidative response to exercise - Bresciani, Guilherme; González-Gallego, Javier; da Cruz, Ivana B.; de Paz, Jose A.; Cuevas, María J. (Clinical biochemistry, 2013)
In humans, the manganese-superoxide dismutase (MnSOD) gene contains a polymorphism (Ala16Val) that has been related to several metabolic dysfunctions and chronic diseases. However, the obtained results suggest that risks related to this polymorphism are directly influenced by environmental factors. Because few studies have analyzed this possible influence, we performed a controlled study to evaluate if the oxidative stress caused by exercise is differentially modulated by the Ala16Val MnSOD polymorphism. Fifty-seven males were previously genotyped and 10 subjects per genotype were selected to perform a bout of controlled intense exercise. MnSOD mRNA expression, protein content, enzyme activity, and total glutathione and thiol content from peripheral blood mononuclear cells were evaluated before and 1h after a bout of intense exercise. The AA genotype participants showed increased post-exercise MnSOD mRNA expression and enzyme activity compared to baseline values. Conversely, MnSOD mRNA expression did not change but protein thiol content decreased significantly after the bout of exercise in VV carriers. A comparison of the genotypes showed that the AA genotype presented a higher MnSOD protein content than VV volunteers after exercise; while a dose-effect for the A allele was found for enzyme activity. This study supports recent evidence that genotypes of key antioxidant enzymes may be associated with differential oxidative stress modulation and the hypothesis that the risk of disease associated with the MnSOD Ala16Val gene polymorphism may be controlled by environmental factors. [Display omitted] ► The Ala16Val MnSOD polymorphism is associated with the risk of chronic disease. ► Evidence supports that these risks are influenced by environmental factors. ► A controlled intense exercise is a reliable model of ROS generation. ► Biochemical responses to exercise were influenced by the Ala16Val polymorphism. ► The results indicate a relevance of Ala16Val MnSOD in oxidative stress modulation.